Assessment of housing affordability problem among young households in Ekurhuleni Municipality and Johannesburg, South Africa - Mawoyo, Kudzai (My University, 2019)
This study examines the issue of Housing Affordability problems faced by the young households in Johannesburg, South Africa. Johannesburg is the heart of various business activities in South Africa, it is characterized by increasing external & internal migration, increasing house prices, inadequate income and an increase in the cost of living. Furthermore, growing unemployment rate in South Africa is one of the key influencing factors to note which makes it a struggle for the YHs to own a house in the housing market. Previous research of similar nature has been conducted before, it was based mainly on housing affordability problems among YHs in the city of Kuala, Malaysia and findings reveal that the main problem faced by the YHs was a limited supply of affordable housing units (Zyed et.al, 2016). South African housing market has been experiencing an increase in limited supply of affordable housing units for the households because contractors want to maximize profits and they prefer medium to high end housing which is costly for the majority of households in South Africa (Rust 2006). Reconstruction and Development Programme housing is present and active in South Africa and it does offer help by providing land and housing to the people of South Africa. However, there is limited government policy interaction in the policy implementation for affordable housing. The study aims to identify HA problems faced by YHs in Ekurhuleni municipalities and the city of Johannesburg, South Africa, which attributed to affordability, housing choice, housing income, housing policy and house prices. This paper adopts a case study approach and design which is then followed by the explanation on data collection and sampling technique, data validity and data analysis. This paper concludes that there is a gap in affordable housing for YHs in the Johannesburg housing market. Empirical evidence reveals that lack of sufficient income in securing a housing loan is also one of the challenges faced by YHs as well as their financial commitments. The supply of affordable housing for YHs is limited and further decreases their opportunity to purchase a house. Affordability problems faced by YHs in Ekurhuleni municipality and the Coj needs critical study that will aid in establishing in right perspective the ability of the YHs in the acquisition of housing units within their income limit.
A research report submitted in partial fulfilment of the requirement for the degree of Master of Science in Building to the School of Construction Economics and Management at the University of the Witwatersrand, Johannesburg, 2019
Keywords: Housing--Planning; Dwellings--Cost effectiveness